PERTUMBUHAN BIBIT KELAPA SAWIT DENGAN APLIKASI ASAP CAIR LIMBAH PELEPAH KELAPA SAWIT - Mila Lukmana; Diah Karunia; Zuliyan Agus Nur Muchlis Majid (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
ABSTRACT The growth of good and quality seeds requires a lot of fertilization, considering that oil palm seeds grow quickly. Generally, the fertilizers used are compound fertilizers and inorganic single fertilizers. Continuous use of inorganic fertilizers without being balanced by organic fertilizers can reduce soil quality. Therefore, alternative fertilizers are needed to reduce the use of inorganic fertilizers. Liquid smoke from palm oil midrib-leaf waste can be developed into organic fertilizer, so a lot of studies are needed. This study aims to determine the growth of oil palm seedlings by giving liquid smoke from palm oil midrib-leaf waste. The treatments given were P0 (0% /control), P1 (2% liquid smoke), P2 (3% liquid smoke), P3 (4% liquid smoke), P4 (5% liquid smoke), P5 (10% liquid smoke ), P6 (15% liquid smoke) and P7 (20% liquid smoke). The results obtained are analyzed. A further BNJ test will be carried out at the 5% level if they give significantly different results. Parameters observed were plant height (cm), number of leaves (strands), leaf area (cm2), and diameter of stem circumference (mm). The application of liquid smoke from the palm fronds had a significant effect on plant height and leaf area of oil palm seedlings, while the parameters of the quantity leaves and stem diameter had no significant effect. The best treatment based on plant height and leaf area parameters was 2% liquid smoke from palm oil midrib-leaf. Keywords:  liquid smoke, palm oil midrib-leaf, palm oil